Construction and analysis of a kinetic model of the ovine adrenal steroidogenic subsystem comprising of CYP17 and 3β-HSD - Van Schalkwyk, Frederick Josephus (Erick) (Stellenbosch : Stellenbosch University, 2016)
ENGLISH ABSTRACT : This study describes: how time-dependent experimental data, describing the reactions catalyzed by ovine cytochrome P450 17α-hydroxylase/17,20-lyase (CYP17), was obtained using pregnenolone and progesterone as substrates ; the construction and validation of a kinetic model and determining the Km and Vmax - values for each reaction catalyzed by ovine CYP17 ; how the time-dependent metabolism of pregnenolone, 17α-hydroxypregnenolone and dehydroepiandrosterone by ovine 3β-hydroxysteroid dehydrogenase (3β-HSD), was obtained ; the construction and validation of a kinetic model and determining the Km and Vmax - values for each reaction catalyzed by ovine 3β-HSD